Pemotongan Sepihak Upah Pekerja Industri Padat Karya Yang Terdampak Perubahan Ekonomi Global Berdasarkan Hukum Ketenagakerjaan - Febrianti Pertiwi, Hana; Karsona, Agus Mulya; Singadimedja, Holyness N. (Fakultas Hukum Universitas Islam Malang, 2025)
Export-oriented labor-intensive industries make an important contribution to the Indonesian economy, and in times of global economic and inflationary turmoil, labor-intensive industries are affected. Minister of Labour Regulation No. 5/2023 provides leeway for affected companies to adjust wages and working hours, but in practice there are cons related to this adjustment. This research is normative juridical research, using statutory and conceptual approaches and collecting legal materials through literature and field studies. The purpose of this research is to find out the form of legal protection for workers based on the Minister of Manpower Regulation Number 5/2023 and the actions taken by the government against employers who fail to fulfill their obligations. Based on the Minister of Labour Regulation No. 5/2023 provides protection for workers and employers where, in wage adjustments, there must be an agreement; companies that fail to meet their obligations can be subject to administrative and criminal sanctions.